1997
DOI: 10.1152/jappl.1997.83.6.1923
|View full text |Cite
|
Sign up to set email alerts
|

Neural-mechanical coupling of breathing in REM sleep

Abstract: During rapid-eye-movement (REM) sleep the ventilatory response to airway occlusion is reduced. Possible mechanisms are reduced chemosensitivity, mechanical impairment of the chest wall secondary to the atonia of REM sleep, or phasic REM events that interrupt or fractionate ongoing diaphragm electromyogram (EMG) activity. To differentiate between these possibilities, we studied three chronically instrumented dogs before, during, and after 15-20 s of airway occlusion during non-REM (NREM) and phasic REM sleep. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…As reported before (Fagenholz et al 1976;Sullivan et al 1979;Coote, 1982;Douglas et al 1982a;Douglas et al 1982b;Berthon-Jones & Sullivan, 1984;Smith et al 1997;Horner et al 2002), the HCVR was similar during non-REM sleep and quiet wake but significantly reduced during REM sleep. We also confirm that hypercapnia does not change f R during REM sleep (Berthon-Jones & Sullivan, 1984;Horner et al 2002;Nakamura et al 2007).…”
Section: Loss Of F R Control Contributes To Reduced Chemoreflex Gain supporting
confidence: 76%
See 1 more Smart Citation
“…As reported before (Fagenholz et al 1976;Sullivan et al 1979;Coote, 1982;Douglas et al 1982a;Douglas et al 1982b;Berthon-Jones & Sullivan, 1984;Smith et al 1997;Horner et al 2002), the HCVR was similar during non-REM sleep and quiet wake but significantly reduced during REM sleep. We also confirm that hypercapnia does not change f R during REM sleep (Berthon-Jones & Sullivan, 1984;Horner et al 2002;Nakamura et al 2007).…”
Section: Loss Of F R Control Contributes To Reduced Chemoreflex Gain supporting
confidence: 76%
“… b ; Berthon‐Jones & Sullivan, ; Smith et al . ; Horner et al . ), the HCVR was similar during non‐REM sleep and quiet wake but significantly reduced during REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…As reported before (Fagenholz et al, 1976;Sullivan et al, 1979;Coote, 1982;Douglas et al, 1982a;Douglas et al, 1982b;Berthon-Jones & Sullivan, 1984;Smith et al, 1997;Horner et al, 2002), the HCVR was similar during non-REM sleep and quiet wake but significantly reduced during REM sleep. We also confirm that hypercapnia does not change f R during REM sleep (Berthon-Jones & Sullivan, 1984;Horner et al, 2002;Nakamura et al, 2007).…”
Section: Loss Of F R Control Contributes To Reduced Chemoreflex Gain supporting
confidence: 76%
“…However, during REM sleep the hypercapnic ventilatory reflex is reduced to only changes in V T and no longer alters breathing frequency (Fagenholz et al, 1976;Sullivan et al, 1979;Coote, 1982;Douglas et al, 1982a;Douglas et al, 1982b;Berthon-Jones & Sullivan, 1984;Smith et al, 1997;Horner et al, 2002). Furthermore, Orem et al (2005) showed that in hyperventilated conscious cats diaphragmatic EMG recordings re-emerged during REM sleep that were absent during non-REM sleep.…”
Section: State-dependent Control Of Respirationmentioning
confidence: 99%
“…Moreover, the apneic and bradycardic responses to instillation of water or inflation of a balloon in the larynx that did not cause arousals were actually more pronounced during REM sleep than NREM sleep (523). The average diaphragmatic response to airway occlusion was reduced during REM sleep when compared to NREM sleep, but further analysis revealed that this occurred only at times when inhibitory effects of REM sleep on diaphragmatic activity predominated, rather than throughout the state (503). In rabbits, reflex activation of the GG muscle was reduced during both NREM sleep and REM sleep to a larger degree than expected from the concomitant suppression of spontaneous GG muscle activity (185).…”
Section: Neurochemically Distinct Central Neuronal Systems With Statementioning
confidence: 99%